Manifest niepoprawności - Bagiński, Dobrosław (Strategie komunikacyjne i procesy twórcze, 2022)
Paper discusses the problem of creativity in scientific research and artistic activity. Based on the reflexions of the eminent (historical and contemporary) scientists and artists, and on the recent research in cognitive psychology Author substantiates the thesis that the essence of authentic creativity, both in science and arts, lies the imagination and deliberate breaking widely shared rules.